Development of gut inflammation in mice colonized with mucosa-associated bacteria from patients with ulcerative colitis. Issue 1 (December 2015) - Du, Zhengyu; Hudcovic, Tomas; Mrazek, Jakub; Kozakova, Hana; Srutkova, Dagmar; Schwarzer, Martin; Tlaskalova-Hogenova, Helena; Kostovcik, Martin; Kverka, Miloslav
Abstract Background Disturbances in the intestinal microbial community (i.e. dysbiosis) or presence of the microbes with deleterious effects on colonic mucosa has been linked to the pathogenesis of inflammatory bowel diseases. However the role of microbiota in induction and progression of ulcerative colitis (UC) has not yet been fully elucidated. Methods Three lines of human microbiota-associated (HMA) mice were established by gavage of colon biopsy from three patients with active UC. The shift in microbial community during its transferring from humans to mice was analyzed by next-generation sequencing using Illumina MiSeq sequencer. Spontaneous or dextran sulfate sodium (DSS)-induced colitis and microbiota composition profiling in germ-free mice and HMA mice over 3–4 generations were assessed to decipher the features of the distinctive and crucial events occurring during microbial colonization and animal reproduction. Results None of the HMA mice developed colitis spontaneously. When treated with DSS, mice in F4 generation of one line of colonized mice (aHMA) developed colitis. Compared to the DSS-resistant earlier generations of aHMA mice, the F4 generation have increased abundance ofClostridium difficile and decrease abundance ofC. symbiosum in their cecum contents measured by denaturing gradient gel electrophoresis and DNA sequencing. Conclusion In our study, mucosa-associated microbes of UC patients were not able to induce spontaneous colitis in gnotobiotic BALB/c mice but they were able to increase the susceptibility to DSS-induced colitis, once the potentially deleterious microbes found a suitable niche.